Acetabular Remodeling and Role of Osteotomy After Closed Reduction of Developmental Dysplasia of the Hip. (1st June 2016) - Shin, Chang Ho; Yoo, Won Joon; Park, Moon Seok; Kim, Jun Ho; Choi, In Ho; Cho, Tae-Joon
Abstract : Background: The purposes of this study were to evaluate acetabular remodeling after closed reduction of developmental dysplasia of the hip (DDH) and to delineate the role of osteotomy. Methods: Eighty-four hips with DDH treated with closed reduction and followed until the patient was 8 years of age or older were included in this study. The mean age at closed reduction was 14.0 months (range, 3 to 30 months) and that at the latest follow-up visit was 12.7 years (range, 8.0 to 24.7 years). Osteotomy was performed in 26 hips (31%) during the follow-up period, at an average age of 2.8 years (range, 2.0 to 5.8 years). The acetabular index (AI) and center-edge angle (CEA) were measured, and osteonecrosis was graded. The treatment outcome was evaluated as satisfactory (Severin grade I or II) or unsatisfactory (III or IV). We retrospectively analyzed the associations among radiographic parameters, performance of osteotomy, grade of osteonecrosis, and final outcome. Results: A satisfactory outcome was observed in 67 (80%) of the 84 hips. An osteotomy was not performed in 30 of 34 hips with an AI of <32° and a CEA of >14° at the age of 3 years, and 28 (93%) of these 30 hips showed a satisfactory outcome. Of the 33 hips with an AI of ≥32° and a CEA of ⩽14° at the age of 3 years, the 20 that had undergone an osteotomy showed a higher proportion of satisfactory outcomes than the 13 hips that had not (p = 0.01). Three of the 4 hips that showed an unsatisfactory outcome following an osteotomy had an AI of ≥34° at 1 year post-osteotomy. Grade-II, III, or IV osteonecrosis, according to the Bucholz-Ogden classification, developed in 10 of the 84 hips, and these 10 hips had a higher proportion of unsatisfactory outcomes than did those that developed no or grade-I osteonecrosis (p = 0.004). Conclusions: Hips with DDH showing poor acetabular remodeling after closed reduction may benefit from osteotomy. The AI and CEA at the age of 3 years can serve as one of the guidelines for osteotomy. Continued surveillance for acetabular remodeling is required even after osteotomy. Level of Evidence: PrognosticLevel III . See Instructions for Authors for a complete description of levels of evidence.